Tensile Behavior of SM520B-1G Plate by SMAW Joint Applied for Elevated Highway Road Construction - Anggraini, Lydia (President University, 2023)
The main objective of this project is to study the mechanical and chemical characteristics of the SM520B welding plate used in the Jakarta-Cikampek Elevated Highway construction. The construction is needed to decrease the high volume of vehicles passing the highway every day. SM520B metal plate is used as the material in the girder box due to high strength and toughness and also good weldability.There are several tests conducted in the lab of PT Biro Klasifikasi Indonesia (Persero), i.e., spark OES test, tensile test, bending test, Charpy impact test, macro hardness test, and macro etch test. Spark OES test result shows that SM520B is low alloy steel with 0.165% carbon content. The SM520B tensile test result determines that the average yield strength, i.e., 503.45 N/mm², and the average tensile strength, i.e., 608.87 N/mm² of SM520B steel plate has met the requirement according to ASTM DS67B standard. The bending test result shows that no crack was found in the welding area. The Charpy impact test results of SM520B Welding plate indicates that high impact energy occurs in the welding area with the highest value of 214,24 J and slowly reduces when approaching close to the fusion line, i.e., 186.08 J. Higher Hardness Vickers value occurs in the HAZ area of SM520B during Vickers hardness, i.e., 235.8 J and the macro etch test result on the welding plate indicate there is no significant crack, porosity, and slag inclusion found in the welding.The main objective of this project is to study the mechanical and chemical characteristics of the SM520B welding plate used in the Jakarta-Cikampek Elevated Highway construction. The construction is needed to decrease the high volume of vehicles passing the highway every day. SM520B metal plate is used as the material in the girder box due to high strength and toughness and also good weldability. There are several tests conducted in the lab of PT Biro Klasifikasi Indonesia (Persero), i.e., spark OES test, tensile test, bending test, Charpy impact test, macro hardness test, and macro etch test. Spark OES test result shows that SM520B is low alloy steel with 0.165% carbon content. The SM520B tensile test result determines that the average yield strength, i.e., 503.45 N/mm², and the average tensile strength, i.e., 608.87 N/mm² of SM520B steel plate has met the requirement according to ASTM DS67B standard. The bending test result shows that no crack was found in the welding area. The Charpy impact test results of SM520B Welding plate indicates that high impact energy occurs in the welding area with the highest value of 214,24 J and slowly reduces when approaching close to the fusion line, i.e., 186.08 J. Higher Hardness Vickers value occurs in the HAZ area of SM520B during Vickers hardness, i.e., 235.8 J and the macro etch test result on the welding plate indicate there is no significant crack, porosity, and slag inclusion found in the welding.